Who is Julia? Teaching audience analysis through the concept of audience persona. Issue 2 (3rd April 2022) - Kopacz, Maria A.
Abstract : Audience analysis is essential for creating successful messages across communication fields. The audience persona is an effective tool for understanding the characteristics and needs of a target audience. Through this unit activity, students experience the process of persona development, build skills in data collection and analysis, and gain in-depth understanding of a specific audience in preparation for subsequent messaging assignments. Courses: Strategic Communication, Public Relations, Content Marketing, Advertising, Public Speaking, Mass Communication, Social Media Communication, Mass Communication Research Methods. Objectives: Through this unit activity, students will be able to (1) apply the principles of audience persona development, (2) build skills in data collection and analysis, and (3) gain in-depth understanding of a core audience group as the basis for crafting effective messages